Regional Head Elections by the People's Representative Council: A Critical Analysis of Constitutionality and Democratic Backsliding - Mawardi Mawardi; Yudhi Hertanto; Patawari Patawari; Jusuf Luturmas; Karman Jaya (CV. AFDIFAL MAJU BERKAH, 2026)
The election of regional heads constitutes a fundamental mechanism for the realization of popular sovereignty and the implementation of decentralization at the local level. Since the post-reform era, the direct election of regional leaders by citizens has been widely regarded as a significant achievement in strengthening local democracy in Indonesia. Nevertheless, the re-emergence of discourse advocating the election of regional heads by Regional People’s Representative Councils (DPRD) has sparked intense debate, particularly from constitutional law and contemporary democratic theory perspectives. This article aims to critically examine the election of regional heads by DPRD by assessing its compatibility with constitutional principles and analyzing its implications within the framework of democratic backsliding. The research employs normative legal methods, utilizing statutory, conceptual, and comparative approaches. The findings indicate that although the election of regional heads by DPRD may formally satisfy procedural democratic requirements, such a mechanism carries a substantial risk of weakening substantive democracy. This is evidenced by the reduction of direct public participation, the increasing influence of political elites and oligarchic structures, and the shift of accountability from the electorate to local legislative bodies. Furthermore, this mechanism is considered inconsistent with the spirit of Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia, which emphasizes the democratic election of regional leaders. Therefore, any alteration to the regional head election system must be approached with caution to ensure that it does not become a vehicle for democratic regression, but rather contributes to the enhancement of legitimacy, public participation, and the overall quality of local democracy.